2018
DOI: 10.1021/acs.jafc.7b05820
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Functional Analysis of CncC and Keap1 Genes in Silkworm

Abstract: CncC/keap1-ARE is an important signaling pathway for detoxification and antioxidation in Diptera and Coleoptera insects. However, such a signaling pathway has not been studied in Bombyx mori. In this study, BmCncC and Bmkeap1 genes were cloned, their amino acid sequences were analyzed, and each functional domain was mapped. Through phylogenetic analysis and sequence comparison among multiple species, we found that the Neh1 motif of CncC was highly conserved and the DLG motif was replaced by the DMG motif in Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…In this study, the larva epidermis became transparent and showed the characteristics of mature larva after high temperature induction (Fig 1A), the survival and pupation rate of silkworm were significantly decreased (Fig 1D), which was in consistent with previous studies [10]. BmCncC/keap1 pathway plays an important role in response to oxidative stress and regulation of antioxidative and detoxification genes expression [22]. Whether this pathway involved in metamorphosis processes and regulates ecdysone-synthesis P450 genes in silkworm have not been reported.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the larva epidermis became transparent and showed the characteristics of mature larva after high temperature induction (Fig 1A), the survival and pupation rate of silkworm were significantly decreased (Fig 1D), which was in consistent with previous studies [10]. BmCncC/keap1 pathway plays an important role in response to oxidative stress and regulation of antioxidative and detoxification genes expression [22]. Whether this pathway involved in metamorphosis processes and regulates ecdysone-synthesis P450 genes in silkworm have not been reported.…”
Section: Discussionsupporting
confidence: 90%
“…Subsequently, upregulation of different detoxification enzymes, especially P450s, by different chemicals were detected in other insects such as the fruit fly (Amichot et al, 1998), the black swallowtail caterpillar (Papilio polyxenes) (Berenbaum et al, 1990), the tobacco hornworm (Snyder et al, 1993), the mosquito Anopheles (Epis et al, 2014;Vontas et al, 2005), the tobacco cutworm (Spodoptera litura) (B. , and the silk moth (Bombyx mori) (J. Hu et al, 2018). In this century, using new transcriptomic strategies such as Micro-array (King-Jones et al, 2006;Le Goff et al, 2006;Lin et al, 2010;Vontas et al, 2005) and RNAseq (Coelho et al, 2015;Simma et al, 2019;Wilding, 2018), a much more complex diversification of insect xenobiotic response systems has been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The domesticated silkworm (Bombyx mori), is a silk insect with enormous economic value for the sericulture industry. China produces more than 78% of raw silk worldwide (Hu et al, 2018). The silk gland synthesizes and secretes silk fibre, which has been widely used in the silk products for thousands of years (Xia et al, 2008).…”
Section: Introductionmentioning
confidence: 99%